Students’ Perceptions Of Using English Songs To Enhance Vocabulary Mastery: A Qualitative Study - Risma Sagala; Selviana Napitupulu (CV. Doki Course and Training, 2026)
Vocabulary mastery is essential in English as a Foreign Language (EFL) learning; however, many EFL learners face difficulties and low motivation when vocabulary instruction relies on conventional teaching methods. This study aims to explore students’ perceptions of the use of English songs as learning media to enhance vocabulary mastery. The research employed a descriptive qualitative design involving 15 students from an English Education program. Data were collected through semi-structured interviews and open-ended questionnaires and analyzed using thematic analysis. The results indicate that students perceive English songs positively in vocabulary learning. The dominant findings show that English songs increase learning motivation, support vocabulary retention through repeated exposure and contextual meaning, and improve pronunciation accuracy. Nevertheless, several challenges were identified, particularly related to unfamiliar vocabulary and song tempo, which require appropriate instructional guidance. In conclusion, the use of English songs contributes meaningfully to vocabulary development in EFL contexts by fostering motivation, retention, and pronunciation improvement when implemented with guided learning strategies.